Use of contraceptive methods among Nursing students from a University of the Northeast (Research, Society and Development, 2021)
This study seeks to analyze the profile of nursing students under the use of contraceptive methods. This is a quantitative, descriptive, cross-sectional study, with 133 participants from the course, from the 1st to the 10th period, enrolled from 2013 to 2017. The data were collected from September to November 2018, through a semi-structured questionnaire. The predominant profile of the participants is presented as: single, with an average age of 23 years, declaring themselves students. Of these, 94% maintain a heterosexual relationship, the sexarche with the highest percentage was 16-20 years old (45%), with the male condom as the most used contraceptive method. Interrupted intercourse (17%) and oral contraceptives (16%) are the most used in the sequence. A large proportion of university students (84.6%) said they had never used the female condom. Of the participants, 8% have already had unplanned pregnancies and 5% have already acquired some STI. It is concluded that the students, despite having easy access to information, still need spaces for sexual health education promoted through the provision of electives, as well as rounds of conversations and workshops related to the theme.